2022
DOI: 10.3389/fneur.2022.825225
|View full text |Cite
|
Sign up to set email alerts
|

EEG Oscillatory Networks in Peri-Ictal Period of Absence Epilepsy

Abstract: ObjectiveTo investigate the dynamical brain network changes before and after an absence seizure episode in absence epilepsy (AE).Methods21 AE patients with a current high frequency of seizures and 21 sex- and age-matched health control (HC) who reported no history of neurological or psychiatric disorders and visited the hospital for routine physical examinations were included. Each included subject underwent a 2-h and 19-channel video EEG examination. For AE patients, five epochs of 10-s EEG data in inter-icta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…Differentiating between ictal and interictal EEG patterns in patients with typical absence seizures has long been a focal point for both clinicians and researchers. Recently, interest has grown in utilizing novel qEEG analysis techniques to further explore these phenomena (Antwi et al, 2019 ; Li et al, 2022 ; Springer et al, 2022 ; Zhong et al, 2022 ). The primary objective of our study was to investigate whether distinguishable differences exist in the spectral and entropy characteristics of EEGs in the pre-ictal and post-ictal periods compared to the interictal interval in a group of patients with typical absence seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiating between ictal and interictal EEG patterns in patients with typical absence seizures has long been a focal point for both clinicians and researchers. Recently, interest has grown in utilizing novel qEEG analysis techniques to further explore these phenomena (Antwi et al, 2019 ; Li et al, 2022 ; Springer et al, 2022 ; Zhong et al, 2022 ). The primary objective of our study was to investigate whether distinguishable differences exist in the spectral and entropy characteristics of EEGs in the pre-ictal and post-ictal periods compared to the interictal interval in a group of patients with typical absence seizures.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have reported findings that lead to the opposite conclusion. For example, Li et al ( 2022 ), found a decrease in delta oscillations from the interictal to the pre-ictal state in a group of 21 patients with CAE. They proposed that this result could be explained by decreased cortical activity associated with slow oscillation in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Common abnormal rhythms observed in EEG mainly include spikes, sharp waves, spike‐slow complexes, sharp‐slow complexes, high rhythm disorders, paroxysmal rhythm waves, and positive spike rhythms, which can be used to identify seizures 4 . A further study found weaker alpha rhythm in the superior frontal gyrus among epilepsy patients compared with healthy people, and as the seizure goes, the delta and theta rhythms both turn to sighter, on contrary with alpha rhythm 39 . Another study reported that synchronization of brain neuronal activity enhanced during seizures, which was owe to decreasing autonomy of brain activity 40 .…”
Section: The Current State In the Field Of Seizure Detection Based On...mentioning
confidence: 91%
“…4 A further study found weaker alpha rhythm in the superior frontal gyrus among epilepsy patients compared with healthy people, and as the seizure goes, the delta and theta rhythms both turn to sighter, on contrary with alpha rhythm. 39 Another study reported that synchronization of brain neuronal activity enhanced during seizures, which was owe to decreasing autonomy of brain activity. 40 The variation of EEG rhythm apparently varies with each type of seizure.…”
Section: Discharge Of Brain Neurons In Seizuresmentioning
confidence: 99%
“…In addition, drug naïve childhood absence epilepsy patients undergo significant alterations in resting-state networks of inter-ictal and ictal periods, resulting in dysfunction of specific networks essential for psychosocial functioning ( 15 ). However, by now, few studies ( 16 , 17 ) have been devoted to investigating the topological organization of functional brain networks in JAE patients with typical 3 Hz discharges and atypical discharges during resting state without the confounding effect of antiepileptic drugs and inter-ictal epileptic discharges.…”
Section: Introductionmentioning
confidence: 99%